From a Cup of Tea to Cardiovascular Care: Vascular Mechanisms of Action - Marios Sagris; Panayotis K. Vlachakis; Spyridon Simantiris; Panagiotis Theofilis; Maria Gerogianni; Paschalis Karakasis; Konstantinos Tsioufis; Dimitris Tousoulis (Life, 2024)
Tea consumption is increasingly recognized for its potential benefits to cardiovascular health. This study reviews the available research, concentrating on the major components of tea and their mechanisms of action in the cardiovascular system. Tea is abundant in bioactive compounds, such as flavonoids and polysaccharides, which possess significant antioxidant and anti-inflammatory properties. These compounds play a crucial role in mitigating oxidative stress and inflammation, thereby supporting cardiovascular health. They enhance endothelial function, leading to improved vascular relaxation and reduced arterial stiffness, and exhibit antithrombotic effects. Additionally, regular tea consumption is potentially associated with better regulation of blood pressure, improved cholesterol profiles, and effective blood sugar control. It has been suggested that incorporating tea into daily dietary habits could be a practical strategy for cardiovascular disease prevention and management. Despite the promising evidence, more rigorous clinical trials are needed to establish standardized consumption recommendations and fully understand long-term effects. This review offers a more comprehensive analysis of the current evidence based on endothelium function and identifies the gaps that future research should address.